Remote management of musculoskeletal pain: a pragmatic approach to the implementation of video and phone consultations in musculoskeletal practice. (15th November 2020) - Hohenschurz-Schmidt, David; Scott, Whitney; Park, Charlie; Christopoulos, Georgios; Vogel, Steven; Draper-Rodi, Jerry
Abstract : Video and phone consultations for musculoskeletal pain are effective, safe, and appreciated by patients. Implementation and execution require special consideration and such guidance is provided. Abstract: Introduction: Remote consultations through phone or video are gaining in importance for the treatment of musculoskeletal pain across a range of health care providers. However, there is a plethora of technical options for practitioners to choose from, and there are various challenges in the adaptation of clinical processes as well as several special considerations regarding regulatory context and patient management. Practitioners are faced with a lack of high-quality peer-reviewed resources to guide the planning and practical implementation of remote consultations. Objectives: This Clinical Update seeks to provide practical guidance for the planning and implementation of remote consultations for the management and treatment of people with musculoskeletal pain. Methods: Recommendations are based on a brief overview of the relevant research regarding phone and video consultations for musculoskeletal practice and derived from the literature, relevant guidelines, and practical experience. Results: The technical feasibility of remote consultations for musculoskeletal complaints is good, patient satisfaction is high, and a growing body of evidence supports its comparative effectiveness to in-person consultations in some circumstances for improving pain and functioning. We consider in detail practical aspects such as the choosing of hardware and software, we touch on the legal and regulatory context, and we focus on the adaptation of clinical processes and communication. Conclusion: This Clinical Update draws together best-practice evidence in a practically applicable format, enabling therapists who are working with people with pain to directly apply this knowledge to their individual clinical settings and the requirements of their patients.